Kesepakatan Damai Mou Helsinki dan Problematika Implementasi Undang-Undang Nomor 11 Tahun 2006 tentang Pemerintahan Aceh - safria purnama; Aisar Riski (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The Aceh conflict was a protracted vertical conflict rooted in the colonial era and extending to the armed resistance of the Free Aceh Movement (GAM) starting in 1976. The conflict formally ended with the signing of the Helsinki Memorandum of Understanding (MoU) on August 15, 2005, which was subsequently institutionalized through Law Number 11 of 2006 concerning the Government of Aceh (UUPA). This study aims to analyze the status of the Helsinki MoU within the implementation of Law Number 11 of 2006 and the challenges faced in implementing the law, particularly regarding the failure to fully realize the substance of the peace agreement. Employing a qualitative method with a literature review approach and drawing on the conflict theories of Dahrendorf and Coser, the study reveals that a militaristic approach failed to quell the conflict, whereas dialogue facilitated by an international third party succeeded in producing a peace agreement. The findings indicate that the Helsinki MoU does not constitute an international treaty between states as defined by the 1969 Vienna Convention; rather, it is a political peace agreement that was transformed into national law through the UUPA. Although the agreement successfully shifted the conflict from armed struggle to the legal-political arena, the implementation of the UUPA continues to face issues such as the curtailment of Aceh's authority, the suboptimal fulfillment of victims' rights, controversies surrounding regional symbols and delays in transitional justice.